2012
DOI: 10.1155/2012/350150
|View full text |Cite
|
Sign up to set email alerts
|

The Results of Search for the Neutrino Magnetic Moment in GEMMA Experiment

Abstract: The result of the neutrino magnetic moment measurement at the Kalinin Nuclear Power Plant (KNPP) with GEMMA spectrometer is presented. The antineutrino-electron scattering is investigated. A high-purity germanium detector with a mass of 1.5 kg placed at a distance of 13.9 m from the 3 GWthreactor core is exposed to the antineutrino flux of2.7×10131/cm2/s. The recoil electron spectra taken in 18134 and 4487 hours for the reactor ON and OFF periods are compared. The upper limit for the neutrino magnetic momentμν… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
203
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(216 citation statements)
references
References 16 publications
6
203
1
Order By: Relevance
“…(7) givesμ ν < 5.1 × 10 −11 , which is close to the bounds µ ν < 5.4 × 10 −11 µ B and µν e < 2.9 × 10 −11 µ B that were obtained from the analysis of solar neutrinos [10] and in the GEMMA laboratory experiment on antineutrino scattering off electrons [11], respectively.…”
supporting
confidence: 82%
“…(7) givesμ ν < 5.1 × 10 −11 , which is close to the bounds µ ν < 5.4 × 10 −11 µ B and µν e < 2.9 × 10 −11 µ B that were obtained from the analysis of solar neutrinos [10] and in the GEMMA laboratory experiment on antineutrino scattering off electrons [11], respectively.…”
supporting
confidence: 82%
“…Also, solar neutrino experiments obtained a limit on the neutrino magnetic moment coming from modifications of the neutrino electroweak cross section. For instance, the GEMMA experiment [14]-which uses a reactor antineutrino flux and analyzes the recoil electron spectra produced from the detection of such an antineutrino flux-has established the limit μ ν < 2.9 × 10 −11 μ B . The experiments Super-Kamiokande [15] and Borexino [16] obtained limits of μ ν < 1.1 × 10 −10 μ B and μ ν < 5.4 × 10 −11 μ B , respectively, by analyzing the spectrum of the solar neutrino flux, which applies for a combination of all neutrino magnetic moment elements.…”
Section: Resultsmentioning
confidence: 99%
“…The best current laboratory limit is given by GEMMA, an experiment measuring the electron recoil of antineutrino-electron scattering near the reactor core. It constrains the effective magnetic moment to be less than 2.9 · 10 −11 µ B [7]. A recent study by Cañas et al [8] showed that results of the solar neutrino experiment Borexino give similar limits.…”
Section: Introductionmentioning
confidence: 90%
“…(2.2) and (2.3). The current best laboratory experimental limit for the NMM is at µ ν ∼ 2.9·10 −11 µ B [7], while neutrino masses above 0.2 eV are in conflict with cosmological observations [9]. Therefore the above estimate shows that generating large NMM while simultaneously keeping the radiative mass correction δm ν low, requires a significant amount of fine-tuning.…”
Section: New Physics Above the Electroweak Scalementioning
confidence: 98%